“Black Birds”: The Vision of the Bombing Raids on Madrid in Spanish and Foreign Poetry of the Civil War (II): Warring Factions, Sexes and Points of View (Castilla. Estudios de Literatura, 2020)
This paper focuses on the analysis of the poems which were written under the influence of the fascist bombing raids on Madrid during the Spanish Civil War. Our point of view is, at the same time, hermeneutic and comparatist, because we have tried to explore these texts with and contrastive analysis of certain dichotomies: insurgent camp versus republican camp, male and female poets, and a personal or testimonial point of view versus a collective or mediated vision.
Keywords: Bombing raids on Madrid; Spanish contemporary poetry; Spanish poetry of the Civil War; Collective memory; Battle of Madrid